Analysis of Students' Learning Interest Using E-LKPD Based on Liveworksheet Class VIII Junior High School - Rosidah, Rosidah; Suyanto, Slamet; Zafrullah, Zafrullah (Journal of Research and Educational Research Evaluation, 2023)
The advancements in science and technology in the 21st century have introduced new challenges in the educational landscape, specifically for teachers during the instructional process. Teachers are expected to provide learning experiences that can attract students' interest in learning. This study aims to describe the learning interest of VIII grade students in science learning media assisted by E-lKPD based on liveworksheet. This type of research is descriptive quantitative. The research sample used was class VIII junior high school students consisting of 20 students taken randomly. The instrument used is a non-test questionnaire of students' interest in learning which consists of 20 statements. The utilized methodology for data analysis involves quantitative descriptive analysis, a technique that provides a detailed summary of the data without running statistical inferences. The results of the analysis of students' learning interest using liveworksheet-based E-LKPD learning media on plant structure and function material based on five indicators of students' learning interest obtained an average of 81.12% with a very good category. The results showed that the response of learning interest of class VIII students on the material of plant structure and function assisted by science learning media assisted by E-LKPD based on liveworksheet received a positive response from students and could increase students' learning interest. The findings of this research are intended to serve as a valuable resource and supplementary learning tool for educators in facilitating interactive learning experiences.